Ozone concentration at various heights near the surface layer in Shenyang, Northeast China - Li, Liguang; Liu, Ningwei; Shen, Lidu; Zhao, Ziqi; Wang, Hongbo; Wang, Yangfeng; Li, Xiaolan; Ma, Yanjun (Frontiers in Environmental Science, 2022)
Ozone pollution has been growing in the recent decade, becoming a critical urban environmental issue in China. However, Shenyang's near-surface ozone concentration (ground to 100 m altitude) is of grave concern. To obtain the ozone concentration and the corresponding meteorological conditions from October 1, 2018, to September 30, 2019, we built observatory sites at low (≈15 m) and high (≈90 m) layers in Shenyang, northeast China. Then, we analyzed the temporal variation of ozone concentration and discussed the relationship between ozone concentration and the meteorological factors at low and high layers. Compared with the high layer, the ozone concentration in the low layer is chartered with an earlier peak and higher diurnal range. The ozone concentration in all seasons peaked at a low-layer height first, early in winter (15:00) and late in summer (17:00). Then, the peak at high-layer height lags behind 1-2 h, generally occurring between 17:00 and 19:00. The variations in ozone concentration at low and high layers differ in daytime and nighttime. The diurnal ranges of ozone concentrations at the low layer are higher than those at the high layer in the four seasons examined. Overall, ozone concentration correlated significantly with air temperature, having correlation coefficients of 0.814 (P < 0.05) in the low layer and 0.731 (P < 0.05) in the high layer. Inversely, it showed a weak correlation with relative humidity: 0.310 (P < 0.05) and 0.351 (P < 0.05) in the low and high layers, respectively. Also, the correlation coefficients with wind speed were meager at both layers. Generally, ozone pollution is not severe in Shenyang.